Islamic philosophy A-Z - Groff, Peter S. (Philosophy A-Z series., 2007)
A unique introductory guide to the rich, complex and diverse tradition of Islamic philosophy. Islamic Philosophy A-Z comprises over 100 concise entries, alphabetically ordered and cross-referenced for easy access. All the essential aspects of Islamic philosophy are covered here: key figures, schools, concepts, topics, and issues. Articles on the Peripatetics, Isma'ilis, Illuminationists, Sufis, kalam theologians and later modern thinkers are supplemented by entries on classical Greek influences as well as Jewish philosophers who lived and worked in the Islamic world. Topical entries cover various issues and key positions in all the major areas of philosophy, making clear why the central problems of Islamic philosophy have been, and remain, matters of rational disputation. This book will prove an indispensable resource to anyone who wishes to gain a better understanding of this fascinating intellectual tradition.